1998
DOI: 10.1016/s0378-1135(98)00219-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Dichelobacter nodosus isolated from footrot in sheep in Malaysia

Abstract: Pulsed field gel electrophoresis analysis of genomic DNA was used to investigate genetic diversity among Dichelobacter nodosus from footrot in sheep in Malaysia. Twelve Dichelobacter nodosus strains isolated from lesion materials from infected sheep were confirmed as Dichelobacter nodosus by polymerase chain reaction technique using the species-specific Dichelobacter nodosus 16S RNA sequence Ac and C as primers. Pulsed field gel electrophoresis banding profiles using restriction enzymes ApaI (5'GGGCCC3'), SfiI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Results of PFGE from the current study are consistent with work done in Malaysia, where 12 isolates of D. nodosus from three epidemiologically unrelated farms had eight different molecular types (24), indicating a high genetic diversity in that D. nodosus population. A study in New Zealand investigated the genetic diversity of D. nodosus using PCR to amplify regions of the fimbrial gene (fimA) and found considerable genetic diversity, with 11 of 15 strains showing differences in fimbria sequences (25).…”
Section: Discussionsupporting
confidence: 88%
“…Results of PFGE from the current study are consistent with work done in Malaysia, where 12 isolates of D. nodosus from three epidemiologically unrelated farms had eight different molecular types (24), indicating a high genetic diversity in that D. nodosus population. A study in New Zealand investigated the genetic diversity of D. nodosus using PCR to amplify regions of the fimbrial gene (fimA) and found considerable genetic diversity, with 11 of 15 strains showing differences in fimbria sequences (25).…”
Section: Discussionsupporting
confidence: 88%
“…Several strain types of D. nodosus have been detected within and between sheep, flocks (7, 9, 13, 14, 1618), and geographic regions (9, 13, 14). It has also been reported that clonal groups persist within farms and regions for decades (9); however, there is little information on the persistence of individual strains within sheep or feet.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have used genotyping for molecular epidemiological investigations of D. nodosus [10-13]. Pulsed field gel electrophoresis (PFGE) is discriminatory and reproducible, and has been used for typing D. nodosus [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed field gel electrophoresis (PFGE) is discriminatory and reproducible, and has been used for typing D. nodosus [10,13]. Typing based on the proline-glycine repeat ( pgr ) gene in D. nodosus was described by Calvo-Bado et al .…”
Section: Introductionmentioning
confidence: 99%